Les enjeux relatifs à la perception et à la communication dans le cadre de la gestion des risques sur la santé publique - Maximilien Debia (Éditions en environnement VertigO, 2003)
Proliferation of technologies and increased implication of the population in various debates related to public health contributed to consider prevention and precaution as important factors in risk management. The latter is a complex process where assessment, perception and communication play a central role. In the perspective of improving transparency and equity considerations, the risk management process must take into account the obligation to set coordination mechanism and iterative approach between risk managers, stakeholders and population.